TEMPERATURE PANAS DAN USIA TERHADAP KELELAHAN PADA PEKERJA DI TEMPAT PEMBUANGAN AKHIR - Trisna Dewita (IDENTIFIKASI, 2020)
This study aims to determine the relationship of heat temperature and age with work fatigue in the area of Punggur Final Disposal Of 2019. This research uses observational analytic research using a cross-sectional approach using quantitative methods. Is a study that studies the relationship between risk factors (independent) with effect factors (dependent), the number of samples in the study amounted to 30 workers. The study was conducted in the area of Punggur Lake in Batam City. The study was measured by using a questionnaire and measuring instruments using the QUEStempº32 Thermal Environment Monitor (measuring hot work environment) ISBB / WBGT results were obtained. Test analysis using the chi-square test. The results of this study obtained the value of P-value for heat, and age less than 0.05. This means that Ho in Reject there is a significant relationship between the factors of Heat Temperature, Age With Work Fatigue. Conclusion There is a Significant Relationship between Heat Temperature and Age on Work Fatigue in workers in the Telaga Punggur TPA area in Batam City in 2019. Suggestions are expected management of Telaga Punggur TPA Providing adequate drinking water and providing sufficient rest periods for workers pedestrians also try to cross to use sidewalk facilities on the other side that are not used to sell traders who have the risk of conflict between pedestrians and vehicles at the crossing point.